Orangia highways (B) - Es?, P?ter; Klibanoff, Peter; Schmedders, Karl; Hunter, Graeme, Dr. (London : Kellogg School of Management, 2006)
In part B of this case students focus on procurement auctions from the bidders' point of view and are asked to develop the optimal bidding strategy in a first-price auction for a risk-neutral bidder and calculate the value of knowing the number of one's opponents.
Originally published in Es?, P., Klibanoff, P., Schmedders, K., & Hunter, G. (2006). Orangia highways (B). 5-106-007(B). Evanston, IL: Kellogg School of Management at Northwestern University.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Road construction contracts -- Case studies; Roads -- Design and construction -- Case studies